Research on picture books: A comparative study of Asia and the World - Wu, Jia-Fen (Malaysian Journal of Library and Information Science, 2019)
A bibliometric analysis of scholarly articles on picture books between 1992 and 2017 portrays both the worldwide and Asian trends based on the development of picture book research for the past 26 years. The findings are based on an analysis of 21,450 references to 619 articles on picture books in 295 journals indexed by the Web of Science. Four composite themes consistently emerge from the analysis are: (a) Reading intervention for young children; (b) Toddlers’ transference through picture book illustrations to the real world; (c) gender equity issues; and (d) Special education concerns. The first two themes centre on early childhood education, whereas the other two focus on human rights. The potential themes in 80 articles, taken from 65 journals, present the inherent characteristics/features found in picture book research among 12 Asian countries. Although results present four core themes that have formed worldwide on the topic over the past 26 years, there are five specific themes generated in the context of this topic in Asia, along with three common themes. Computer-assisted instruction and educational technology are seen to be a potential trend in future picture book research related to Asia.